Trade Unions and 'Europe': Are the Members out of Step? - Richard Hyman (London School of Economics and Political Science (LSE), European Institute, 2010)
The 'no' vote in the Irish referendum of June 2008 on the Lisbon Treaty – reversed in October 2009 – threw the European Union into crisis. Yet it reflected a familiar pattern of popular rejection of initiatives on European integration. This article provides an overview of such referendums in western Europe (unfortunately, the author lacks the linguistic competence to cover most post-2004 member states). It is evident that while mainstream trade unions (or at least their leaders) have usually endorsed the integration process, in most countries where referendums have been held their members have voted otherwise. Such rejection has often been based on 'progressive' rather than 'reactionary' grounds. Popular attitudes are malleable, but it requires a major strategic re-orientation if unions are to reconnect with their members in order to build a popular movement for a genuinely social Europe.
Keywords: 330